Prevalence of naso-pharyngeal Pneumococcal colonization in children between 1 to 5 years old in pre-school educative centers. 2014-2015 - Dunia María Chavez Amaro; María Felicia Casanova González; María Eugenia Toledo Romaní; Nivaldo Linares Pérez; Gilda Toraño Peraza; Martha Montes de Oca Rivero (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: Streptococcus pneumoniae is part of the normal bacterial flora of the nasal and pharingeal mucosa. Naso-pharyngeal colonization precedes the pneumococcal disease and affected individuals are a reservoir at the community level. Objective: to determine the prevalence of global naso-pharyngeal colonization and by serotypes of Streptococcus pneumoniae in children of pre-school age before anti pneumoccocal vaccination. Methods: a cross descriptive study in the Cienfuegos Municipality, within the period of June 2014 and April 2015. in children aged between 1 and 5 years attending preschool educative centers (N=1 129). Samples of naso-pharyngeal exudates were taken following the set guidelines. The prevalence of colonization was estimated and the most frequent serotypes were identified. Results: the global prevalence of naso-pharyngeal colonization was 32,32 %. The most frequent vaccine serotypes were 19F (6,02 %) and 6B (3,99 %); of those related with the vaccine, 6A predominated (5,49 %) and of the not related to the vaccine the most frequently observed was 14B. Conclusion: naso-pharyngeal colonization in preschool children not vaccinated against pneumoccocus presented a high prevalence at the expense of the serotypes included in the conjugated anti-peumococcal vaccines.